Diabetes Mellitus and Diabetic Nephropathy - Carpio Troya, Ana Cecilia (2023)
Diabetes mellitus encompasses a group of diseases characterized by hyperglycemia due to alterations in the secretion or action of insulin in the body. Treatment is a fundamental factor in the search for patient improvement and the prevention of future complications, for which factors such as exercise or a balanced diet can be used to support treatment. The aim of this study was to update medical-scientific information on the management and prevention of complications of diabetes mellitus. A bibliographic search was carried out in the main databases with inclusion and exclusion criteria in recent years. Among the results found, authors specified that the profile of the diabetic patient should be taken into account in order to take preventive measures in terms of exercise and diet. In addition, information on new oral treatments for T2DM (type 2 diabetes mellitus) and their mechanisms of action has been reported. It is therefore clear that good treatment and prevention measures must be adjusted to the profile of each patient for the benefit of their overall wellbeing.